EVALUATION OF HEALTH IN CHILDREN LIVING IN REGION WITH DEVELOPED CEMENT INDUSTRY - M.V. Kudin; A.V. Skripkin; Yu.N. Fedorov (Вопросы современной педиатрии)
Evaluation of health state in children living in the city with developed cement industry showed presence of pre-nosological forms of ecologically conditioned diseases coming into being as a result of exposure with salts of heavy metals in cement dust. Key words: children, cement dust, bronchial asthma, pneumoconiosis, dermatosis, crystaluria, nephropathy, gestosis.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(5):42-47)